Exclusion Reloaded: The Chronicles of Covid-19 on Students with Disabilities in a South African Open Distance Learning Context - Ngubane-Mokiwa, S.A.; Zongozz, J.N. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Students with disabilities have been going through different forms of discrimination and exclusion. These include inaccessible learning materials and learning platforms, negative attitudes from lecturers, fellow students and more. This paper comes from a qualitative study that sought to explore how Covid-19 deepened these educational inequalities at an Open Distance Learning institution in South Africa. The results of the study reveal that institutions of higher learning had to quickly adjust their teaching and assessment to online mode. This led to heightened exclusion of students with disabilities as their examinations had to be postponed to second semester due to lack of preparations for special examinations. Students also reported experiencing extra pressure as they had to write double the examinations at the end of the year. Some students reported lack of access to assistive technologies which they normally borrow from the library, this was because the Post Office was not operating during the National Lockdown Level 5. The novel nature of Covid-19 is such that the real barriers it caused on people and students with disabilities in particular and it will keep revealing itself gradually. This paper ends by making recommendations on how an ODL institution could accommodate the needs of students with disabilities to enhance their learning experiences during pandemics or natural disasters.